2022
DOI: 10.3389/fpubh.2022.854687
|View full text |Cite
|
Sign up to set email alerts
|

Sociodemographic and Occupational Factors Associated With Burnout: A Study Among Frontline Healthcare Workers During the COVID-19 Pandemic

Abstract: PurposeTo describe the prevalence of burnout among frontline healthcare workers (HCWs) during the COVID-19 pandemic and the associated sociodemographic and occupational factors.MethodsA cross sectional survey study was carried out to study HCWs burnout using the 19-item Full Copenhagen Burnout Inventory (CBI) that includes personal, work, and patient-related burnout subscales. Bivariate analysis was used to test for associations and p < 0.05 was considered statistically significant.ResultsA total of 207… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 70 publications
(91 reference statements)
1
11
0
Order By: Relevance
“…This section included 20 questions involving the three dimensions of emotional exhaustion (questions 1-5), negative detachment (questions 6-12), and self-efficacy (questions [13][14][15][16][17][18][19][20]. The questionnaire was rated on a 5-point Likert scale, with 0 indicating never and 4 indicating every day or more, and the higher the score the higher the burnout.…”
Section: Burnout Scalementioning
confidence: 99%
See 1 more Smart Citation
“…This section included 20 questions involving the three dimensions of emotional exhaustion (questions 1-5), negative detachment (questions 6-12), and self-efficacy (questions [13][14][15][16][17][18][19][20]. The questionnaire was rated on a 5-point Likert scale, with 0 indicating never and 4 indicating every day or more, and the higher the score the higher the burnout.…”
Section: Burnout Scalementioning
confidence: 99%
“…Thus, burnout may be a long-term process of resource depletion and inadequate response to chronic work stress ( 15 ). Aljabr argues that identifying the demographic and occupational influencing factors of burnout during the COVID-19 pandemic helps plan psychological support strategies ( 16 ).…”
Section: Introductionmentioning
confidence: 99%
“…Physiological diseases include hypertension, neurasthenia, dyspepsia, and impaired immune function [ 18 , 19 , 20 ]. Psychological symptoms include depression, anxiety, and job burnout [ 21 , 22 ], which reduce employees’ coping ability. Social behavior abnormal is manifested as avoiding work, absenteeism, and medical accidents [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the measured means of PB and WB in India [ 84 ] and Lithuania [ 85 ] during the COVID-19 pandemic were 49.72 ± 18.68, 39.69 ± 20.43, 45.27 ± 17.77, and 46.41 ± 17.16. Notably, an anonymous self-administered questionnaire broadcasted via WhatsApp and Twitter for healthcare workers during the COVID-19 pandemic demonstrated that the means of PB and WB even reached 67.23 ± 21.66 and 61.38 ± 21.60 [ 86 ]. Obviously, different countries and regions may experience varying levels of overall burnout among due to differences in medical culture and environment.…”
Section: Discussionmentioning
confidence: 99%